Estudo do perfil epidemiológico do melanoma cutâneo na cidade de Jaú-SP através do registro de base populacional - Veneziano, Donaldo Botelho [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: The cutaneous melanoma is the most aggressive of the skin cancers. Its incidence is increasing all over the world and many factors are being assigned to this increase. Studies on cutaneous melanoma based on population-based registries are scarce in Brazil. Objectives: Describe the incidence rates (1996-2011) by cutaneous melanoma in the city of Jaú, according: sex, year of the diagnosis, age, anatomic location, stage and histological type. Describe the mortality coefficients (1996-2011) by cutaneous melanoma in the city of Jaú, according: sex, year of death and age. Analyze the tendency of the incidence coefficients (1996-2011), according: year of diagnosis, sex and stage. Analyze the tendency of the mortality coefficients (1996-2011) by cutaneous melanoma in the city of Jaú, according: year of death and sex. Methods: 162 new cases of cutaneous melanoma diagnosed in the period from 1996 to 2011 were analyzed and they were provided by the Population-Based Cancer Registry of Jaú and 39 deaths by cutaneous melanoma occurred between 1996 and 2011 provided by the Mortality Information System of the Ministry of Health (SIM-MS). The crude and the standardized coefficients of incidence and mortality were calculated, the tendency of those coefficients were analyzed through the regression model. Results: The average incidence coefficient (1996-2011) for the feminine sex was 5.1 from 100,000 and for the masculine sex was 4.8 from 100,000. Both didn’t present tendency of increasing or decreasing in the period (stability). The average mortality coefficient (1996-2011) for the feminine sex was 1.4 from 100,000 and for the masculine sex was 2.2 from 100,000, both also didn’t present tendency of increasing or decreasing. The incidence coefficients for the cases diagnosed in the initial phase of the disease, stage 0, presented growing tendency (r2=0.73; p=0.03) and the cases of stage I and II, presented decreasing tendency (r2=0.98; ...

Introdução: O melanoma cutâneo é o mais agressivo dos cânceres de pele. Sua incidência vem aumentando em todo o mundo e vários fatores têm sido atribuídos a este aumento. Estudos sobre o melanoma cutâneo com base em dados de registros populacionais são escassos no Brasil. Objetivos: Descrever os coeficientes de incidência (1996-2011) por melanoma cutâneo na cidade de Jaú, segundo: sexo, ano de diagnóstico, faixa etária, localização anatômica, estadio e tipo histológico. Descrever os coeficientes de mortalidade (1996-2011) por melanoma cutâneo na cidade de Jaú, segundo: sexo, ano do óbito e faixa etária. Analisar a tendência dos coeficientes de incidência (1996-2011), segundo: ano de diagnóstico, sexo e estadio. Analisar a tendência dos coeficientes de mortalidade (1996-2011) por melanoma cutâneo na cidade de Jaú, segundo: ano do óbito e sexo. Métodos: Foram analisados 162 casos novos de melanoma cutâneo diagnosticados no período de 1996 a 2011 fornecidos pelo Registro de Câncer de Base Populacional de Jahu e 39 óbitos por melanoma cutâneo ocorridos entre 1996 e 2011 fornecidos pelo Sistema de Informações sobre Mortalidade do Ministério da Saúde (SIM-MS). Foram calculados os coeficientes bruto e padronizado de incidência e de mortalidade, foi analisada a tendência destes coeficientes através do modelo de regressão. Resultados: O coeficiente médio de incidência (1996-2011) para o sexo feminino foi de 5,1 por 100.000 e para o sexo masculino foi de 4,8 por 100.000. Ambos não apresentaram tendência de crescimento ou queda no período (estabilidade). O coeficiente médio de mortalidade (1996-2011) para o sexo feminino foi de 1,4 por 100.000 e para o sexo masculino foi de 2,2 por 100.000, ambos também não apresentaram tendência de crescimento ou queda. Os coeficientes de incidência para os casos diagnosticados na fase inicial da doença, estadio 0, apresentaram tendencia de crescimento (r2=0,73; ...
Keywords: Pele - Cancer; Melanoma; Epidemiologia - Pesquisa; Mortalidade; Epidemiology Research Methodology